Vitamin A Deficiency after Gastric Bypass Surgery: An Underreported Postoperative Complication - Kerstyn C. Zalesin; Wendy M. Miller; Barry Franklin; Dharani Mudugal; Avdesh Rao Buragadda; Judith Boura; Katherine Nori-Janosz; David L. Chengelis; Kevin R. Krause; Peter A. McCullough (Hindawi Limited, 2011)
Introduction. Few data are available on vitamin A deficiency in the gastric bypass population. Methods. We performed a retrospective chart review of gastric bypass patients (n=69, 74% female). The relationship between serum vitamin A concentration and markers of protein metabolism at 6-weeks and 1-year post-operative were assessed. Results. The average weight loss at 6-weeks and 1-year following surgery was 20.1±9.1 kg and 44.1±17.1 kg, respectively. At 6 weeks and 1 year after surgery, 35% and 18% of patients were vitamin A deficient, (<325 mcg/L). Similarly, 34% and 19% had low pre-albumin levels (<18 mg/dL), at these time intervals. Vitamin A directly correlated with pre-albumin levels at 6 weeks (r=0.67, P<0.001) and 1-year (r=0.67,  P<0.0001). There was no correlation between the roux limb length measurement and pre-albumin or vitamin A serum concentrations at these post-operative follow-ups. Vitamin A levels and markers of liver function testing were also unrelated. Conclusion. Vitamin A deficiency is common after bariatric surgery and is associated with a low serum concentration of pre-albumin. This fat-soluble vitamin should be measured in patients who have undergone gastric bypass surgery and deficiency should be suspected in those with evidence of protein-calorie malnutrition.